Teenager’s decision making on online shop shopping in the time pandemic: Choice or compulsion - Febrianti, Arzela; Hidayati, Dewi Ayu (C-DISC, 2025)
The rapidly spreading phenomenon of the covid-19 pandemic has given positive growth to the development of e-markets. The restrictions on physical contact that are applied make people prefer shopping in e-markets or online shopping, but teenagers’ decision making to shop online is not always due to compulsion. The purpose of this research is to see how teenagers who are students of SMA Negeri 1 Blambangan Umpu Way Kanan Regency make decisions in shopping online. The method used in this research is a qualitative method with a phenomenological approach. The results showed that teenagers in making decisions to do online shopping during the covid pandemic were more due to choice rather than coercion with the existence of Large-Scale Social Restrictions (PSBB) rules. They make this decision as a choice because so far they have been accustomed to doing online shopping compared to offline, besides that there are many conveniences that are generated by doing this online shopping. Teenagers’ motivation in doing online shopping is divided into two, namely internal motivation and external motivation. Internal motivation comes from pleasure, hobbies and habits. While external motivation comes from the influence of family, friends and social media.